Formulation of Digested Beverage Cans and Iron Plate Wastes as a Coagulant for Adequate Hygiene of Fresh River Water - Mutiara Gita; Elva Stiawan; Hotma Renta; Mayang Fauziah Putri Kuntjahjono; Aura Puja Lestari (Indonesian Journal of Chemical Studies, 2025)
In terms of hygiene and sanitation, ensuring the availability of qualified water for those purposes remains challenging to perform under certain conditions. Accordingly, efforts to provide simple water processing technology are ongoing and innovatively developed. This study displayed an innovative approach to producing coagulants for water processing by utilizing metal salts obtained synthetically from used beverage cans and iron plates through the electrolysis principle and characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and Scanning Electron Microscopy - The Energy Dispersive X-ray (SEM-EDX), subsequently. After mixing with calcium hypochlorite and adding to water sample, subsequently, the coagulant showed the ability to reduce the turbidity level and several categories of impurities, i.e., nitrate, nitrite, dissolved Manganese, Cr6+ ion, and microbial levels. Future research and development in formulating coagulants derived from digested beverage cans and iron plate wastes hold significant potential to advance sustainable and efficient water treatment technologies, ensuring improved hygienic quality of fresh river water while contributing to waste valorization and environmental protection.